SAFETY ATTITUDES IN OBSTETRICS AND GYNAECOLOGY TRAINEES IN LABOUR ROOM PRACTICES: EXPERIENCE AT DOW UNIVERSITY OF HEALTH SCIENCES - Ala, Syed Hasan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the safety attitudes of labour room practices of FCPS residents. Study Design: Mixed method sequential study. Place and Duration of Study: Department of Obstetrics and Gynaecology unit I and unit II, Civil Hospital Karachi/Dow University of Health Sciences, from Oct 2017 to Feb 2018. Methodology: The first phase of the study was collection of quantitative data using a Safety attitude questionnaire followed by second phase of two focus group discussions. Quantitative data was computed and analysed in SPSS-19, while qualitative data was transcribed involved verbatim followed by coding of the data with thematic analysis. Results: A total of 79 residents were approached out of which 69 consented to participate in the study yielding a response rate of 87.3% (69/79). The total mean domain scores of SAQ were highest for stress recognition domain (63.7 ± 18.1), while the least domain scores were for job satisfaction (60.5 ± 15.9). Amongst, year one and year four residents the mean domain scores were highest for working condition domain (68.8 ± 20.2), (64.1 ± 10.9) respectively. It has been endorsed in FGD that there was good collaboration among doctors however supporting staff were not sufficient in number, in addition their behavior was unprofessional and irresponsible. There was compromised cleanliness and insufficient medical supplies to fulfill the needs of huge number of patients. Conclusion: The safety attitudes of FCPS residents, showed positivity towards Job satisfaction, safety climate and team work, however excess work load, stress and communication gaps are negatively affecting the safety...